2003
DOI: 10.1063/1.1557373
|View full text |Cite
|
Sign up to set email alerts
|

Design of Curie point written magnetoresistance random access memory cells

Abstract: Very high density magnetoresistance random access memory (MRAM) cells may be subject to thermal upset. This article describes designs that enhance thermal stability and increase ultimate density by using the combination of heat and magnetic field for writing data. The basic storage mechanism can be shape anisotropy, the coupling between an antiferromagnetic layer and a ferromagnetic layer, or a combination of the two. Two designs are described in this article. The first uses a low Curie point material with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…A number of alternative memory technologies, namely magnetic random access memory (MRAM) and ferroelectric RAM (FeRAM) have achieved higher programming performance than fl ash, but scaling-down these technologies remains challenging. [ 3,4 ] Recently, ferroelectric tunnel junction (FTJ) devices emerged as an alternative memory technology, attracting much attention of solid-state physicists and materials scientists. Conceptualized in the 1970s by Esaki et al, [ 5 ] it has been experimentally demonstrated that when an ultrathin ferroelectric fi lm serves as barrier layer in tunnel junction devices, the quantum-mechanical tunneling current and resistance can be manipulated nondestructively via the polarization direction of the ferroelectric Figure 1 c also shows that the layer between the silicon and the STO is amorphous.…”
Section: Doi: 101002/adma201402527mentioning
confidence: 99%
“…A number of alternative memory technologies, namely magnetic random access memory (MRAM) and ferroelectric RAM (FeRAM) have achieved higher programming performance than fl ash, but scaling-down these technologies remains challenging. [ 3,4 ] Recently, ferroelectric tunnel junction (FTJ) devices emerged as an alternative memory technology, attracting much attention of solid-state physicists and materials scientists. Conceptualized in the 1970s by Esaki et al, [ 5 ] it has been experimentally demonstrated that when an ultrathin ferroelectric fi lm serves as barrier layer in tunnel junction devices, the quantum-mechanical tunneling current and resistance can be manipulated nondestructively via the polarization direction of the ferroelectric Figure 1 c also shows that the layer between the silicon and the STO is amorphous.…”
Section: Doi: 101002/adma201402527mentioning
confidence: 99%
“…There are many possible designs proposed in the literature for the MRAM cell, where the heating method or the thermal dependence of the magnetic properties of the MRAM cell varies: low Curie point design [38], exchange biased storage layer [37,40], perpendicular ferromagnetic layer [41]. Furthermore, the heating is achieved either by passing the current through the sense and/or word lines [38,39] or by sending the current directly through the junction [40]. A first design proposed by Daughton and co-workers [38,42] uses a low Curie point ferromagnetic cell with shape anisotropy.…”
Section: Thermally Assisted Mrammentioning
confidence: 99%
“…An alternative write scheme is to assist thermally the switching of the magnetization [37][38][39][40]. This approach is based upon the reduction by heating of the required switching fields.…”
Section: Thermally Assisted Mrammentioning
confidence: 99%
“…Daughton in Nonvolatile Electronics Inc. has suggested Curie point (or Neel point) writing MRAM cell structures [9,19,20], where electrical heating from the currents in the word lines are used to heat the magnetic element above the magnetic ordering temperatures. The cross-section, as shown in Fig.…”
Section: Thermal-assisted Switchingmentioning
confidence: 99%
“…Thermal assisted writing scheme : (a) Curie point writing MRAM[19] and (b) blocking temperature writing MRAM[22].…”
mentioning
confidence: 99%